The Strategic Role of Archives in Public Services in the Licensing Sector - Permana, Danny (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2024)
In the current digital era, archive management plays a strategic role in ensuring the efficiency and effectiveness of public services, especially in the licensing sector. Challenges in archival systems that are not yet integrated and limited access to information are the main obstacles to a fast and accurate licensing process. Optimizing archives is needed to support transparency, and accountability and improve the quality of public services. This research aims to examine the strategic role of archives in public services in the licensing sector and identify archive management strategies to support the efficiency of the licensing process. A descriptive qualitative approach was used in this research, with data obtained from relevant literature studies and interviews with archival practitioners. The conclusion of this research shows that effective and integrated archive management is the main key to speeding up the licensing process and improving the quality of public services. Digitization of archives and the application of information technology has been proven to increase information accessibility and operational efficiency. Apart from that, standardization of records management and human resource training are important factors in increasing competence in modern records management. Cooperation between agencies is also needed to ensure the effective integration of archival systems. Thus, optimizing archives has great potential to support the transformation of public services that are more responsive and quality.